Perencanaan Strategis Sistem Informasi Pada PT. Cakra Prima Nusantara Menggunakan Metode Ward and Peppard - Nicholas Roy Biantoro; Dicky Pratama (Arcitech: Journal of Computer Science and Artificial Intelligence, 2026)
Prior studies applying the Ward and Peppard framework to logistics firms have been confined to standalone, internally-scoped ecosystems, leaving a research gap in cross-organizational IS/IT alignment with a national principal platform. This study addresses that gap by formulating a Strategic Information Systems Plan (SISP) for PT Cakra Prima Nusantara, an authorized distributor of Pupuk Sriwidjaja in South Sumatra, whose operations suffer from data fragmentation due to manual inventory recording, an unintegrated accounting system, and fleet coordination reliant solely on instant messaging. Employing a qualitative case study approach, data were collected through structured interviews, field observation, and document review, then analyzed using the Ward and Peppard framework encompassing Value Chain, PESTEL, SWOT, Critical Success Factors (CSF), and McFarlan Strategic Grid. The study produces an IS/IT blueprint — the Cakra Integrated Distribution System (CIDS) — integrating all internal operational units via cloud architecture and synchronizing fertilizer quota data in real-time with the principal's Distribution Planning and Control System (DPCS) through an API Gateway. This research scope covers strategic planning up to the roadmap and application portfolio stage, not system implementation. The principal contribution to SISP literature lies in demonstrating how the Ward and Peppard framework can be adapted for inter-organizational IS alignment within subsidized commodity distribution, a context underexplored in existing studies.